KAJIAN REFLEKTIF TERHADAP PERPUSTAKAAN ISLAM DI BAGHDAD PADA ERA KLASIK KEBUDAYAAN ARAB-ISLAM KOSMOPOLITAN - Nurdin Laugu (Al Qalam, 2009)
This article is aimed at understanding the issues of Islamic libraries living around the, classical age of cosmopolitan Arab-Islamic culture and their roles in the development of Muslim society. The study is, therefore, focused on investigating the kinds of the Islamic libraries and then on classifying the contribution based on the construction of historical accounts. The investigation found at least five kinds of Islamic libraries, namely: mosque libraries, rulers and their family libraries, madrasah libraries, scholar/private libraries, and university/ academic libraries. Afterwards, the study concludes that the libraries had played important roles as centers for, education and learning, center for translation, centers for research, experimentation, and observation, centers for study and discussion, center for cultural development and preservation, and centers for knowledge/ scientific development and information.